Animal Nutrition and Productions - Simeanu, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The externalization of animals' genetic potential is determined by a number of external factors, of which feeding plays a major role. Animals' nourishment is one of the most important levers to ensure the efficiency of animal production due to both the high share of feed costs in the total cost of products and the influence this has on the growth, reproduction, and health of animals as well as the quality of products obtained from these. This field is one of the most dynamic in the field of husbandry sciences due to the takeover and permanent use of numerous results obtained from research on energy metabolism and nutrients related to the composition of feed and its influence on animal products. This is also due to the great advances in genetics, which create new types of animals with increasing productive potential, but also with different food requirements. This Special Issue collated innovative papers on animal nutrition, physiology, chemistry, biochemistry, genetics, reproduction, and breeding technologies. The articles covered a wide range of topics related to feed quality, the influence of food on the production level, the quality of production, and also on animals' health.